Numerical study of heat and mass transfer during ignition of thermal decomposition products of a coal particle; MATEC Web of Conferences; Vol. 19 : The 2nd International Youth Forum "Smart Grids", Tomsk, Russia, October 6-10, 2014 - Glushkov D. O. Dmitry Olegovich (2014, 2014)
Title screen